Effectiveness of University-Based Educational Interventions on Adaptive Functioning and Employment Readiness of Students with Mild Intellectual Disability - Ushie, Godwin Beshibeshebe; Akpo, Francis Akpo; Emogor, Elogbo Eno; Wonah, Fidelis Aduma; Patrick, Elizabeth Odije; Anthony, Godwin Bullem; Udayi, Eucharia Alorye; Ayep, Isaac Ellah; Ukah, Ukah Julius; Uzu, Florence Nguungwan; Agbogo, Regina Agor; Swem, Terfa; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
Background: Inclusive higher education is increasingly recognized as a pathway for enhancing functional independence and employment outcomes among students with mild intellectual disability. University-based educational interventions aim to support adaptive functioning (AF) and employment readiness (ER); however, empirical evidence regarding their effectiveness in Nigerian universities remains limited. Objective: This study examined the perceived impact of university-based educational interventions on AF and ER among students with mild intellectual disability and explored whether these domains jointly predict overall intervention effectiveness. Methods: A quantitative descriptive research design was employed. Structured questionnaires were administered to 92 students; 84 were completed and returned, yielding a response rate of 91.3%. Among respondents, 46 were male, and 38 were female; all were included in the analyses. Descriptive statistics summarized perceived outcomes of interventions, while multiple regression analysis examined the predictive relationship between AF, ER, and overall intervention effectiveness. Results: The findings indicated that university-based interventions were associated with perceived improvements in communication, problem-solving, social interaction, self-care, task completion, and engagement with career support services. The independent t-test analyses showed no significant differences in overall AF by gender or ER by age, though minor item-level variations were observed. While AF and ER individually reflected positive outcomes, their combined effect did not significantly predict overall intervention effectiveness, suggesting that additional contextual and programmatic factors influence perceptions of success. Conclusion: University-based educational interventions contribute meaningfully to the development of adaptive and employment-related skills among students with mild intellectual disability. The findings highlight the importance of a holistic approach that integrates academic instruction, vocational preparation, social support, and institutional resources to enhance overall program effectiveness. Overall, students perceive these interventions as beneficial in promoting independence, practical skills, and workforce preparedness.